High power diode laser surface melting of SUS 420F steel: investigations on the microstructural, and mechanical properties. (2016) - Sivanandham, N.; Rajadurai, A.; Shariff, S.M.; Senthilselvan, J.; Mahalingam, A.
This research work deals with studies on the laser surface melting (LSM) of SUS 420F plastic mould steel by a high power diode laser (HPDL). The laser treated samples were investigated by optical microscopy, high resolution scanning electron microscopy (HRSEM) and X-ray diffractometry (XRD), and the hardness profiles of the laser surface melting layers were evaluated by a Vickers hardness tester. The plastic mould steel, on surface melting with HPDL contains columnar dendrite and fine martensite microstructure with residual austenite phases. The microstructure transformed from columnar dendrite to randomly oriented ones, as the power was increased from 2 to 3 kW. XRD phase analysis confirmed the formation of martensite and M23 C6 carbide phases at near surface regions of laser treated steel. The high power laser treatment increased the hardness to around 700 HV and wear resistance of the steel was also found to be increased.